1965
DOI: 10.1071/ph650635
|View full text |Cite
|
Sign up to set email alerts
|

A Linear Polarization Survey of the Southern Sky at 408 MC/S

Abstract: SummaryThe results of 408 Mcts linear polarization observations of the southern sky using the 210 ft steerable reflector at Parkes are presented. Combination of this survey with the northern sky survey of the Leiden group shows that almost all of the. polarization at this frequency lies in a band about 60° wide, which contains the great circle that passes through the galactic poles and intersects the plane at lil = 340° and 160°. This large-scale distribution of linear polarization at 408 Mcts may be explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…A general and remarkable result (see Sect. 5) is that (Brouw & Spoelstra 1976) and of the Parkes southern sky survey (Mathewson & Milne 1965). Unfortunately, the vector length has a different scale in the two original figures, therefore only a direct comparison of the direction is feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general and remarkable result (see Sect. 5) is that (Brouw & Spoelstra 1976) and of the Parkes southern sky survey (Mathewson & Milne 1965). Unfortunately, the vector length has a different scale in the two original figures, therefore only a direct comparison of the direction is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…A linear polarization survey of the Southern sky had previously been carried out at 408 MHz using the Parkes telescope (Mathewson & Milne 1965); unfortunately these data have never been put in digital form. In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a limited number of short-baselines are available in this mode and sensitivity is compromised to provide them. Single dish polarimetric observations at long wavelengths provide access to large-scale structure but so far there has only been one such observation (Mathewson & Milne 1965) and it suffered from poor sensitivity and spatial sampling. Furthermore, single dish observations below 300 MHz also lack resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The polarization of the diffuse radio emission that was finally discovered in 1962 had a long period of quiescence after the surveys of Wielebinski & Shakeshaft (1964), Mathewson & Milne (1965) and Brouw & Spoelstra (1976) have been published. The follow-up investigation by Spoelstra (1984) concluded that the Rotation Measure (RM) in the ISM towards l = 140…”
Section: Radio Continuum Polarizationmentioning
confidence: 99%